PENCUCIAN BATUBARA MENGGUNAKAN CHANCE CONE DENGAN MEDIA PASIR BESI - Hendri P. Perangin-angin (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2019)
Study of coal washing was conducted by designing and creating chance cone equipment which was then continued by process performance test using iron sand as a separator medium. The variable used for this experiment was feed coal with the size of -12.5 +5 mm; -5mm +1.68 mm ; and -1.68 mm +0.85 mm, a mixer with a spinning speed of 44, 53, 72, 96, and 120 rpm, and a media relative density ( suspension of water and iron sand ) of 1.3 and 1.4 . From the result of sink – float test, the initial coal ash level of 7.91%, 5.73%, and 6.76% each was obtained. From the result of equipment performance test, the highest efficiency was obtained at 1.4 media relative density of 69.18% at mixer speed of 120rpm with bait size of -1,68 +0,85 mm and ash content of 6,39%.